ANALYSIS OF COUPLED INTERPOLATIVE KANNAN-TYPE CONTRACTION MAPPINGS IN METRIC SPACES - Ogunwe, Festus Tope; Adeniji, Adenike Olusola; Mogbonju, Morufu Mogbolagade; Ogunlusi, Taiwo; Ajibade, Felix Damilola (FUDMA Journal of Sciences, 2026)
Many Researchers have used the notion of interpolative Kannan contraction due to its wider range in applications and its flexibility, rather than the normal Banach contraction. This paper studies the existence, uniqueness, and convergence of fixed points for coupled interpolative Kannan-type contractions in metric spaces. Using Picard and Mann iterative schemes, sufficient conditions ensuring convergence to a unique fixed point are established. The results extend and generalize several existing findings in fixed-point theory.
Keywords: Coupled fixed point; Interpolative Kannan contraction; Metric space; Picard iteration; Uniqueness; Mann iteration